2021
DOI: 10.11591/ijeecs.v21.i3.pp1332-1340
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine-equipped android interface-based heart rate monitoring

Abstract: <p>This research aimed to design a device that can monitor heart rate and help nurses or doctors when they need to monitor and retrieve data of patients. By utilizing Android as a displayer makes it easier for nurses to minimize data retrieval time. The principle of the tool is to record the heart rate data received by the ear clip sensor to be processed by the Atmega328 microcontroller, then displayed on the oled LCD and sent to Android phones via HC-05 Bluetooth for display. If the heart rate data is b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These studies suggested that the mobile application can be developed and improved to diagnose hypertension. This point of view is supported by the studies conducted for a mobile application that are designed for hypertension and health management [43]- [45]. Besides, the computational process of the diagnosis can be placed in the cloud-based system to ensure data processing performance [46]- [50] and overcome the low computational memory in wearable devices [27].…”
Section: Discussionmentioning
confidence: 97%
“…These studies suggested that the mobile application can be developed and improved to diagnose hypertension. This point of view is supported by the studies conducted for a mobile application that are designed for hypertension and health management [43]- [45]. Besides, the computational process of the diagnosis can be placed in the cloud-based system to ensure data processing performance [46]- [50] and overcome the low computational memory in wearable devices [27].…”
Section: Discussionmentioning
confidence: 97%
“…In any scenario, if critical information for treating and diagnosing patients was foreseen in advance, clinicians would have a lot simpler time collecting it. Heart illness is frequently misdiagnosed as coronary artery disease [2], [3]. The main contribution of the paper is as follows:  This research has more significant work for tracking and establishing numerous health monitoring apps.…”
Section: Introductionmentioning
confidence: 99%